**Answer:**

B)Oy+ 3 = 4(x - 1)

Equation of the straight line y +3 = 4( x-1)

**Step-by-step explanation:**

<u><em>**Explanation:-**</em></u>

<u><em>**Step(i):-**</em></u>

Given that the equation y = 4x +2

and given that the point (1,-3)

The equation of the parallel line to the given line

ax +by +k=0

4x-y +k=0

This line is passing through the point (1,-3)

⇒ 4(1) -(-3) +k=0

⇒ 4+3 +k=0

7 +k=0

k =-7

The equation of the Parallel line 4x-y -7 = 0

<u><em>**Step(ii):-**</em></u>

Given that the slope m = 4 and the point (1,-3)

Equation of the straight line

y - y₁ = m(x-x₁)

y -(-3) = 4( x-1)

y +3 = 4( x-1)